2016
DOI: 10.7869/tg.316
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heme oxygenase 1 protects hepatocytes from Isoniazid – Rifampicin induced cell death: an in vitro study

Abstract: Background: Anti tuberculosis therapy agent isoniazid (INH) and rifampicin (RMP) injure hepatocytes. Heme oxygenase-1(HO-1) is a stress induced protein which seems to have some cellular protective function. We examined the protective function of HO-1 during INH-RMP induced cell death of hepatocytes by induction of HO-1 using hemin chloride or by silencing HO-1 gene using small interfering RNA (siRNA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…NQO1 reduced RIF‐Q to RIF and mediated the redox cycle of RIF‐Q‐induced ROS formation and caused cytotoxicity in HepG2 cells . These findings indicated that HO‐1 and NQO1 may play major roles in responding to oxidative stress and alleviating injury caused by ROS, which may at least partly contribute to the underlying pathogenesis of ATLI …”
Section: What Is Known and Objectivementioning
confidence: 93%
See 2 more Smart Citations
“…NQO1 reduced RIF‐Q to RIF and mediated the redox cycle of RIF‐Q‐induced ROS formation and caused cytotoxicity in HepG2 cells . These findings indicated that HO‐1 and NQO1 may play major roles in responding to oxidative stress and alleviating injury caused by ROS, which may at least partly contribute to the underlying pathogenesis of ATLI …”
Section: What Is Known and Objectivementioning
confidence: 93%
“…Heme oxygenase 1 (HO‐1, encoded by the HMOX1 gene) is a phase II antioxidant enzyme that is primarily involved in detoxification, and NRF2 knockdown reduces the basal level of HO‐1 expression . Coadministration of INH and RIF in HepG2 cells could induce expression of the cytoplasmic HO‐1 protein during early hours of drug treatment with minimum loss of cell viability and cell death, and induction of HO‐1 by hemin chloride could ameliorate INH‐RIF‐induced hepatocyte cell death . Sagittaria sagittifolia L. polysaccharide (SSP) significantly alleviated the hepatotoxicity induced by coadministration of INH and RIF in mice, which was mainly attributed to an increase in the gene and protein expression of NRF2 and its downstream enzymes HO‐1 induced by SSP .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…These reactive metabolites could induce the production of excessive reactive oxygen species (ROS), leading to lipid peroxidation and cell death (115). Otterbein et al, have demonstrated that co-administration of Isoniazid (INH) and rifampin (RIF) to HepG2 cells could induce expression of the cytoplasmic HO-1 protein during the early hours of drug treatment, with minimum loss of cell viability and cell death, and induction of HO-1 by hemin chloride could reverse the drug induced liver injury (116). This could be a potential target for a future therapeutic option to counteract INH-RIF drug-induced liver injury.…”
Section: The Modulators and Inducers Of Ho-1mentioning
confidence: 99%